DETERMINANNYA SOSIAL TERHADAP KEJADIAN STUNTING PADA BALITA: TINJAUAN EPIDEMIOLOGI DI PROVINSI NUSA TENGGARA BARAT - Laily Indrayanti Yusuf; Ng Phi Shi; Wahyu Nur Chalamsa; Sunanto, Sunanto; Muhamad Sardiman; Yuly Peristiowati (Bajang Institute, 2025)
Objective: This article aims to analyze the social determinants influencing stunting in West Nusa Tenggara (NTB) Province using an epidemiological perspective and the WHO's Social Determinants of Health (SDH) framework. This analysis is expected to provide a comprehensive overview of the social factors contributing to the high prevalence of stunting in NTB. Methods: This research is a narrative review conducted through a literature search in Google Scholar, PubMed, DOAJ, and ScienceDirect databases, as well as official reports such as Riskesdas, SSGI, the NTB Health Profile, and national policy documents. The articles analyzed were selected based on their relevance to the topic of social determinants of stunting in the past 10 years. A literature synthesis was conducted to identify key themes of social determinants contributing to stunting in NTB. Results: The analysis indicates that stunting in NTB is influenced by a number of interrelated social determinants, particularly poverty, low maternal education, limited access to clean water, poor sanitation, inadequate parenting and feeding practices, early marriage, and unequal access to health services. Environmental factors such as drought and household food security contribute to exacerbating children's vulnerability to chronic malnutrition. These social determinants form a complex network of upstream and downstream factors that influence child growth in NTB. Implications: These findings emphasize that efforts to reduce stunting in NTB must be carried out through a multisectoral approach that focuses not only on direct nutrition interventions but also on improving socioeconomic factors, sanitation, health access, women's education, and policies to prevent child marriage. Upstream interventions targeting structural factors need to be strengthened to create long-term impact. Limitations: As a narrative review study, this research relies on the quality and comprehensiveness of the available literature. Specific data for NTB in recent years still vary across sources, requiring careful interpretation. This study did not include quantitative analysis or meta-analysis, thus not providing an estimate of the strength of the relationship between variables.